QSAR, Molecular Docking and Dynamics Studies of Quinazoline Derivatives as Inhibitor of Phosphatidylinositol 3-Kinase - Muhammad Arba, Ruslin, Waode Umi Kalsum, Armid Alroem, Muhammad Zakir Muzakkar, Ida Usman, Daryono Hadi Tjahjono (Journal of Applied Pharmaceutical Science, 2018)
Phosphatidylinositol 3-kinase (PI3K) plays a prominent role in regulating various crucial cellular functions. Many studies have indicated the involvement of PI3K in tumorigenesis. In the current study, thirty-one quinazoline derivatives were utilized to build a Quantitative Structure-Activity Relationship (QSAR) model which correlates structural feature with PI3K inhibition. The statistically robust QSAR model is pIC50 = 2.515 + 0.000005 (AM1_Eele) + 0.004 (AM1_HF) + 1.170 (AM1_LUMO) − 0.117 (apol) + 0.003 (ASA_H) with a leave-one-out cross-validation coefficient (q2) of 0.6058 and external validation (R2pred) of 0.7725. A novel compound (SC25) was proposed based on the validated QSAR model. Molecular docking of the ligand on PI3K revealed the similar binding mode of SC25 and parent compound ((S)-C5) as well as native ligand (2NQ). Molecular dynamics simulation of 40 ns confirmed the conformational stability of each SC25, (S)-C5, and 2NQ, complexed with PI3K. Prediction of affinity using MM-PBSA method revealed that SC25 has a comparable affinity with that of (S)-C5 and better than that of 2NQ.
Keywords: Docking, MM-PBSA, Molecular dynamics simulation, Phosphatidylinositol 3-kinase, QSAR, Quinazoline.